Effects of pre-fattening weight on production efficiency: A case study of fattening swamp buffalo by farmers - Wichaporn, Jakkit; Klamrak, Monpak; Thannithi, Wiranut; Saengwong, Sureeporn; Intawicha, Payungsuk (Health Science, Science and Technology Reviews, 2022)
The purpose of this study was determined the effects of pre-fattening weight on the production efficiency, data was collected from the farms of local farmers in Phayao Province for 3 production groups: 1) seventy buffalo average weight 203.11±5.77 kg. 2) sixty-three buffalo average weight 254.84±8.64 kg. 3) eighty-five buffalo average weight 317.27±21.08 kg. Buffalos were feed with roughages such as rice straw and napier grass, concentrated feed and water ad libitum. Result shown that group 1 have an average daily gain (ADG) 1.22±0.07 bester than group 2 1.12±0.07 kg/day and group 3 0.86±0.18 kg/day. The average profit per production cycle of buffalo group 1, 2 and 3 had a 4,225.66, 6,229.37 and 4,751.18 baht per head, respectively. Buffalo fattening is another way to earn income for farmers in Phayao province.